DOPO “BARONI IN LAGUNA” (UNICApress, 2026)
This volume is the result of the research project “Dopo baroni in laguna,” funded by the Region of Sardinia and carried out by the Associazione Paesaggio Gramsci as part of a collaboration agreement with the Departments of Humanities, Languages, and Cultural Heritage, and of Economics and Business. Through the essays it contains, the book reconstructs the transformations, stories, and memories of work in the lagoon and the life of the communities of Cabras, Terralba, and Santa Giusta over the past forty-five years: since the spotlight, which had shone on that area during the anti-feudal struggles recounted by Peppino Fiori and later by Ugo Dessy, faded. The book presents the results of research conducted in the area with the involvement of fishermen, cooperatives, community members, and administrators, primarily adopting an oral history perspective complemented by linguistic and economic studies. What emerges, from a grassroots perspective, are the transformations undergone over the last sixty years by the region and the communities that inhabit it, and above all the collective memories within those communities regarding workers’ struggles, the significance of fishing work, generational transitions, and relationships with institutions, the environment, and tourism. More broadly speaking, in a context where the social and economic history of 20th-century Sardinia has yet to be written, this book contributes to broadening and deepening our historical understanding of the island in the modern era.